2018
DOI: 10.17306/j.afs.0516
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic activity of stigmasteryl esters and products of their thermo-oxidative degradation against drug sensitive and drug resistant human acute lymphoblastic leukemia cells

Abstract: Background. Phytosterols are mainly known as a cholesterol-lowering factor, although they form oxidation products during food storage and processing. Moreover, phytosterol oxidation products (POP) can be absorbed and found in human serum, so there is the need to investigate their impact on different kinds of cells. Material and methods. Esters of fatty acids (oleic, linoleic and linolenic) with stigmasterol were synthetized and heated at 180°C, for 1-12 hours. The cytotoxic effect on the leukemic cells of unhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The heated ST-OA did not induce cytotoxic and genotoxic effects nor elevate the intracellular ROS level in normal human colon cells. Similarly, the different cytotoxic potency of thermally treated ST-LA and ST-OA was also observed in human acute lymphoblastic leukemia cell cultures 38 . The higher ST-LA reactivity was probably due to the 2.3-fold higher content of SOPs 25 .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The heated ST-OA did not induce cytotoxic and genotoxic effects nor elevate the intracellular ROS level in normal human colon cells. Similarly, the different cytotoxic potency of thermally treated ST-LA and ST-OA was also observed in human acute lymphoblastic leukemia cell cultures 38 . The higher ST-LA reactivity was probably due to the 2.3-fold higher content of SOPs 25 .…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have shown that free ST is degraded rapidly, generating a diverse group of thermo-oxidative degradation products and oxyderivatives 21 , 25 which may exhibit significant oxidative reactivity and induce cytotoxic and genotoxic effects in normal human cells as demonstrated in the presented studies. It was found that ST esterification with oleic and linoleic acids limited ST degradation and the formation of oxidized sterols, degradation products, and oligomers 25 , 38 , leading to a reduction in the risk of adverse toxic effects. Cytotoxicity experiments proved the lower cytotoxic potential of stigmasteryl esters (ST-OA and ST-LA) than free ST, regardless of whether they were subjected to thermo-oxidative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Raczyk et al. ( 80 ) examined the cytotoxic effect of three stigmasteryl esters on leukemia cells using MTT assay, and they found that the stigmasteryl linoleate had the greatest cytotoxic effect. Nazemi et al.…”
Section: Role Of Stigmasterol In Different Cancersmentioning
confidence: 99%